Finite Element Study on Shear Performances of In-filled Bolt Joint of Assembled GRC Wall with Light Steel Skeleton Frame. Issue 4 (May 2019) - Tang, Zhirong; Zha, Xiaoxiong; Wang, Baolin
Abstract: A new in-filled wall is used in assembled steel structure buildings, which consists of two layers of glass fiber reinforced concrete (GRC) panels and a built-in light steel skeleton frame. To make this new wall fill in the main steel structure, a new in-filled bolt joint is used. In order to obtain the mechanical properties and failure modes under shear load, the shear performances of this joint were studied with the finite element (FE) software ABAQUS. The results show that before reaching the fracture failure strain, the in-filled bolt joint shows good elastic-plastic behaviour. When the strain of the in-filled bolt joint reaches the failure strain, the shear load reaches the peak value. Subsequently, due to the shear fracture of the bolt, the shear load drops rapidly. Throughout the loading process, the stress of steel beam and rectangular steel tube is always very small and the stress of the joint yields in a large area in the later stage.